Exploratory Factor Analysis (EFA) for Lifelong Learning Competencies of Students with Disabilities in University - Arini, Fitri Dwi; Nugraheni, Permata Primadhita (Universitas Negeri Padang, 2024)
This study utilized Exploratory Factor Analysis (EFA) to identify the core factors that constitute lifelong learning competencies among students with disabilities in a university context. This study aimed to evaluate the content validity and perform Exploratory Factor Analysis (EFA) on a 14-item scale designed to assess lifelong learning competencies in students with disabilities. The items were developed based on five key factors: Goal setting, application of knowledge and skills, self-direction and self-evaluation, locating information, and adaptable learning strategies Analyzing the responses of 46 students with disabilities, the study validated the content of the 14 items on the Lifelong Learning Competencies scale. However, the EFA process indicated that only these 10 items could be consolidated into theoretical factors, resulting in four key dimensions: curiosity, openness to learning, access to information and information literacy, and self-direction and self-evaluation. These factors encapsulate critical elements of lifelong learning competencies, including self-regulation, critical thinking, and adaptability. The findings underscore the necessity for universities to implement inclusive strategies that nurture these competencies, thereby fostering an environment conducive to the success of students with disabilities. This research contributes to the advancement of inclusive educational practices, ensuring that students with disabilities are equipped to thrive in lifelong learning and achieve academic and professional success.